Site-directed mutagenesis on plasmid using polymerase chain reaction - Ahmad, Abdul Aziz; Mohd. Salleh, Hamzah; Noorbatcha, Ibrahim Ali (Springer Nature, 2018)
Site-directed mutagenesis (SDM) is a very useful technique to study changes in protein function that may occur as a result of the DNA manipulation. A detail procedure to employ SDM on whole plasmid using polymerase chain reaction (PCR) with successful application of the method on a pET28a plasmid harboring an endoglucanase I gene from Fusarium oxysporum is described here.